Mengenal Pemikiran Islam Liberal - Lukmanul Hakim; Mohd Nasir Omar (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
The Islamic liberal thought is a new school in Islamic thought that comes up to respond the current image of Islam associated with violence, radicalism, and terrorism. However, with the flexibility approach on Islamic normative position the new emerging school of thought to face against Islamic traditionalist or fundamentalist group. It raises pro and con arguments on the liberal thought. Put the debate alone, this article is not aimed to stand on one side to the other rather than to describe the Islamic liberal thought academically and object. The discussion covers the definition, aim, and epistemology of Islamic liberal. The urgency of this study is reflected through assumption of observers on Islamic thought who go with or against the presence of Islamic liberal thought without posing well understanding about the basic concept of the thought.